2017
DOI: 10.1016/j.jconrel.2017.02.024
|View full text |Cite
|
Sign up to set email alerts
|

Rational design of polyarginine nanocapsules intended to help peptides overcoming intestinal barriers

Abstract: The aim of this work was to rationally design and characterize nanocapsules (NCs) composed of an oily core and a polyarginine (PARG) shell, intended for oral peptide delivery. The cationic polyaminoacid, PARG, and the oily core components were selected based on their penetration enhancing properties. Insulin was adopted as a model peptide to assess the performance of the NCs. After screening numerous formulation variables, including different oils and surfactants, we defined a composition consisting of oleic a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 47 publications
1
42
0
Order By: Relevance
“…42 Furthermore, OA was added to modify the fluidity of LNCs and permeabilize cell membrane for enhanced LNCcell interaction and intestinal transport. 43,44 The reduction in heating-cooling range during LNC formation could be explained by OA-induced fluidization of the surfactant monolayer 45 and partial incorporation of some OA molecules into the surfactant film of the microemulsion phase. 46 MFS was incorporated for enhancing LNC structural integrity and imparting membrane activity.…”
Section: Discussionmentioning
confidence: 99%
“…42 Furthermore, OA was added to modify the fluidity of LNCs and permeabilize cell membrane for enhanced LNCcell interaction and intestinal transport. 43,44 The reduction in heating-cooling range during LNC formation could be explained by OA-induced fluidization of the surfactant monolayer 45 and partial incorporation of some OA molecules into the surfactant film of the microemulsion phase. 46 MFS was incorporated for enhancing LNC structural integrity and imparting membrane activity.…”
Section: Discussionmentioning
confidence: 99%
“…Poly-L-arginine (PLA) is the homopeptide of L-arginine, which has been used in medical applications for many centuries due to its cellular penetrating properties. [33][34][35][36][37][38][39] Additionally, it is a semi-essential amino-acid with various roles such as in cell metabolism, wound healing, protein synthesis, and it also shows antimicrobial and antitumor activity. [40][41][42][43][44][45] In particular, owing to their favorable properties, NPs comprised of PLA have garnered considerable interest for delivery of small molecules.…”
Section: Introductionmentioning
confidence: 99%
“…For example, our results have shown the possibility of increasing the corneal penetration of drugs associated to the NCs. 6,25 Similarly, we have found that polymeric NCs led to an enhancement of the systemic absorption of peptide and protein drugs administered by the oral 11,15,16 or nasal 14,26 routes.…”
mentioning
confidence: 91%
“…Due to their lipidic core, NCs were, originally, conceived as suitable carriers for lipophilic drugs. However, our lab has expanded this technology to allow NCs to carry hydrosoluble macromolecules, such as proteins, peptides, and polynucleotides, using them in different therapeutic areas. For example, in the oncology field, we have developed different polymeric NCs containing the cytotoxic drugs plitidepsin and docetaxel, which were able to prolong the blood circulation time of these drugs and reduce their toxicity.…”
Section: Introductionmentioning
confidence: 99%